Transperineal laser ablation of the prostate with EchoLaser™ system: perioperative and short-term functional and sexual outcomes - Sessa, Francesco; Polverino, Paolo; Bisegna, Claudio; Siena, Giampaolo; Lo Re, Mattia; Spatafora, Pietro; Pecoraro, Alessio; Rivetti, Anna; Conte, Francesco Lupo; Cocci, Andrea; Villari, Donata; Minervini, Andrea; et al. (Frontiers in Urology, 2022)
Objective: To date, several ultra-minimally-invasive surgical techniques are available for the treatment of male LUTS due to benign prostatic obstruction (BPO). Herein we report our pre-liminary experience with SoracteLiteTM TPLA for the treatment of carefully selected patients with LUTS due to BPO. Methods: Data from all consecutive patients undergoing TPLA at our institution between April 2021 and February 2022 were prospectively collected in a specific database. Data re-garding functional and sexual outcomes evaluated by validated questionnaires and uroflow-metry were analyzed. All the procedure were performed in an outpatient setting, under local anesthesia and conscious sedation, using EchoLaser device, a multisource diode laser genera-tor. Results: Overall, 38 patients underwent TPLA at our institution during the study period. The median prostate volume was 46 ml (IQR 38-71). The median time to complete the procedure was 31 min (IQR 28-37). All patients but one were discharged within 8 hours of hospital stay. No perioperative Clavien-Dindo grade >2 complications were recorded. Median improvement in Qmax was 17%, 24% and 32% at 1 month, 3 months and last follow-up after surgery; as a result, the median postoperative IPSS at 1 month, 3 months and at last follow-up decreased by -14%, -36% and -35%, respectively. All patients preserved ejaculatory and sexual function. Two patients (5%), catheter carriers before the procedure, experienced acute urinary retention after TPLA treatment and required replacement of an indwelling catheter. Conclusions: TPLA can be a feasible, safe and effective ultra-minimally-invasive procedure for carefully selected patients with LUTS due to BPO.